Dioscorea bulbifera flour: a technological alternative for valuing the tuber available in the Amazon (Research, Society and Development, 2021)
Dioscorea bulbifera is a source of essential nutrients for the maintenance of human health. However, its technological use for the preparation of food products is still little explored. The objective of this work was to prepare D. bulbifera flour (FDB) and evaluate its physicochemical, microbiological and functional characteristics. The tubers were harvested in a domestic establishment in Manaus-AM, submitted to drying in an oven, crushed and sieved. In the flour obtained, the physicochemical composition (moisture, ash, lipids, fiber, proteins, carbohydrates, caloric value, pH and acidity) and microbiological quality (Escherichia coli, Salmonella sp., molds and yeasts) were evaluated. The following functional properties were also determined: water absorption capacity (CAA), oil absorption capacity (CAO), swelling capacity (CI), foam capacity (CE), foam stability (EE) and bulk density (DA). FDB presented the following proximate composition: moisture (5.27%), ash (3.44%), lipids (0.93%), fibers (0.94%), proteins (7.72%), carbohydrates (81.70%) and energy value (366.05 kcal/100g). The pH and titratable acidity means were 0.31% and 6.58, respectively. There was low growth of mold and yeast (1 x 102 CFU/g) and no presence of E. coli and Salmonella sp. The technological properties verified were: CCA (114.63%), CAO (62%), CI (212.44%), CE (8%), EE (98.10%) and DA (0.20g/mL). Dioscorea bulbifera from the Amazon is a promising raw material for obtaining a flour formulation with potential characteristics for use in the food industry, especially in the bakery sector.